The Determinants of Islamic Capital Markets Performance in Asia Pacific Countries: Is the Global Islamic Capital Market Important? - Abid Djazulia; Canderab; Belliwati Kosimc; Cici Sapirad (Migration Letters, 2023)
Research aims: This study was aimed to determine the impact of inflation and exchange rates on capital market performance as reflected in Sharia Stock Index and the role of global Sharia capital market as reflected in Dow Jones Sharia Index as a moderator variable. Design/methodology/approach: This study used associative research. The population of this study consist of 244 Islamic capital markets in Asia Pacific countries; the sample size for this study was 10. The sampling technique used purposive sampling; while moderating regression analysis (MRA) was used in data analysis to test the hypothesis. Research findings: the results of the analysis found that the global sharia stock index can significantly moderate the relationship between inflation and the sharia stock index in Asia Pacific countries. This moderation is negative, meaning that the global sharia stock index weakens this relationship. The global sharia stock index can insignificantly moderate the relationship between the exchange rate and the sharia stock index in Asia Pacific countries. Theoretical contribution/originality: These findings can be used as a reference for the capital market to attract investors. Particularly by taking into account the macroeconomic conditions and stock prices applicable to the global Dow Jones index. Research limitations/implications: This study was conducted only for Asia Pacific Shariah Stock Index, that only have very limited complete reports.